Morphometry and Mortality of Nile Tilapia fingerlings in two different treatments with temperature - Nunes Rodrigues, Marília Danyelle; Calabuig, Cecilia Perez; Gutierrez, Harold Julian Perez; Almeida, Diones Bender; Moreira, Carla Giovane Ávila; Acosta, Izani Bonel; Raposo, Josiane Bones; Moreira, Heden Luiz Marques (Varia Scientia Agrárias, 2014)
The objective of this work is to present the mortality rates of Nile Tilapia (Oreochromis niloticus) subjected to two different temperature treatments, the morphometric measurements and body mass in two different phases in terms of age for each temperature and, morphologically identify differences that may be attributed to sexual dimorphism and that will determine the best age to collect animals for gonads analysis. Two treatments with water temperature were performed: 35° C and 25° C. Animals were killed in two steps: 35° C (71 and 92 days after hatching) and 25° C (112 and 131 days after hatching). The mortality record was performed by direct visualization, morphometry and weighing. The sexing was performed by gonadal histopathology. The treatment at 35° C showed lower mortality indicating that the fish would be more suited to higher temperatures. In contrast, the treatment at 25° C showed significant difference between variables and males with when the animals were 131 days after hatching. Through the morphometric data analysis, animals aged less than 131 days after hatching are morphologically able to gonadal identification on the Supreme strain.